Partisipasi Masyarakat Dalam Pengelolaan Hutan Mangrove di Kecamatan Wori Kabupaten MInahasa Utara - Manginsela, Meyka Prayanti; Egam, Pingkan Peggy; Sondakh, Julianus (Fraktal : Jurnal Arsitektur, Kota dan Sains, 2024)
Mangrove forests are an ecosystem that has a very important function for the environment. Wori District has several areas that have mangrove forests, namely the villages of Tiwoho, Wori, Kima Bajo, Minaesa, Budo, Darunu, Bulo, Pontoh, Lansa, Lantung, Kulu, Mantehage and Nain . Of the several villages in Wori District, Tiwoho Village and Wori Village are included in the conservation area managed by the Bunaken National Park Office. The management of the mangrove forests in Wori District is not yet running completely well, therefore community participation is very necessary in managing the mangrove forest areas. This research aims to determine the form of community participation in mangrove forest management and to determine the level of community participation in mangrove forest management. This research uses qualitative methods with data collection carried out through direct observation, interviews and documentation. The data obtained was then analyzed using Cohen and Uphouff's theory and Arnstein's theory, to see the extent of involvement in the form and level of community participation in mangrove forest management. The results show that community participation is at low and high levels of participation which are included in the categories of therapy, reassurance, partnership, delegation and community control. Mangrove forest management requires the involvement of various parties in the form of planning, implementation, utilization and evaluation to encourage increased community participation in mangrove forest management. Keywords: Community Participation, Management, Mangrove Forests